Pengaruh Pendidikan Kesehatan Tentang Penyakit HIV/AIDS Terhadap Tingkat Pengetahuan Siswa di SMK YPT Banjarmasin Tahun 2023 - Elfika, Elfika; Trifianingsih, Dyah; Warjiman (Journal of Nursing Invention, 2023)
Background: HIV/AIDS is an infectious disease that occurs in society, The high incidence of HIV/AIDS in adolescents is caused by a lack of knowledge and information.  Health education holds an important role in increasing the youth's knowledge of HIV/AIDS prevention, good awareness and knowledge of HIV/AIDS, and a positive attitude are very important for HIV/AIDS prevention. Objective: To analyze the influence of Health Education on Students' Knowledge levels at SMK YPT Banjarmasin. Methodology: This type of research is a pre-experimental design with a one-group pretest-posttest design.  The population of this study were all students in classes X and XI.  The sample for this research was 132 respondents taken using the Consecutive sampling technique.  The research instruments used are questionnaires and health education with power points and leaflets.  Data were analyzed using paired t-tests. Results:The results showed that the level of knowledge before being given health education was good for 3 respondents (2.2%), sufficient for 30 respondents (22.7%), and insufficient for 99 respondents (75%).  The level of knowledge after being given health education was lacking by 5 respondents (3.8%), sufficient by 29 respondents (21.9%), and good by 98 respondents (74.2%).  The results of the paired T-test show a significance value of P-Value 0.000 < 0.05 Conclusion: There is an influence of health education on the level of knowledge of students at SMK YPT Banjarmasin regarding HIV/AIDS.